Gender, entrepreneurship, and coping with the COVID‐19 pandemic: The case of GoFood merchants in Indonesia. Issue 3 (7th December 2022) - Elhan‐Kayalar, Yesim; Sawada, Yasuyuki; van der Meulen Rodgers, Yana
Abstract: This paper examines business performance and crisis‐mitigation strategies among micro, small, and medium‐sized enterprises (MSMEs) in Indonesia during the COVID‐19 pandemic. We utilise a new primary dataset based on administrative records, survey data, and follow‐up interviews with merchants using the digital application GoFood, an on‐demand cooked food delivery service. Three empirical findings emerge: first, the overall employment size of women‐owned businesses shrank more than men‐owned businesses after the onset of the pandemic; second, women were more likely than men to cut personal expenditures and use government assistance as crisis‐mitigation strategies; and third, competition increased sharply as new merchants entered the platform, with the service areas of both incumbents and entrants shrinking over time. These results have implications for policies on womenʼs entrepreneurship, the uptake of business development services, and financing programs for MSMEs.